Predicting Indonesia’s Micro Small Medium Entreprises Stock Price - Purnomo, Singgih; Nurmalitasari, Nurmalitasari; Nurchim, Nurchim; Awang Long, Zalizah (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
The impact of stock prices on new enterprises, notably Micro, Small, and Medium Enterprises (MSMEs), in Indonesia is significant. Given the significance of stock prices for MSMEs, engaging in stock price forecasting is crucial. Several stock price forecast-ing models exist, but only a limited number are suitable for predicting stock prices using limited samples, such as the stock prices of MSMEs in Indonesia. The limited sample size is because MSMEs are newly established enterprises accessing stock prices. This study aims to predict MSME stock prices in Indonesia, namely SOUL and TGUK. The forecasting model utilized is ARIMA. The results suggest that the ARIMA (0,1,1) model provides the most precise forecast for the stock price of SOUL MSMEs, while the ARIMA (1,1,2) model yields the most outstanding performance for TGUK. Investors can use the forecast results to identify profit-able investment opportunities or protect their portfolios from po-tential losses. Moreover, companies can employ stock price pre-dictions to evaluate their performance, develop financial plans, and allocate resources.